MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Siti Qiftiyatul Muzdalifah; Savitri Suryandari; Mahyuni Rahayu (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The study aims to determine the application of interactive learning articulate storyline 3 in increasing the learning motivation of students in class III C SDN Pakis 1 Surabaya. Students of class III C SDN Pakis 1 Surabaya. The type of research is Classroom Action Research Classroom Action Research, which was designed in two cycles and using the Kemmis and Taggart model in the form of a spiral cycle. model of Kemmis and Taggart in the form of a spiral cycle. Each cycle consists of four stages, namely: planning, implementation, observation/evaluation and reflection. reflection. The research subjects were students of class III C SDN Pakis 1 Surabaya. totaling 28 students. The instrument used is a learning motivation questionnaire. Based on the results of pre-cycle observations, the average percentage of questionnaire scores learning motivation of 28 students is 53.5% categorized as moderate. While cycle I observation data has an increase in the average percentage of questionnaire scores to 79% so that it is in the good category. In the last cycle, namely cycle II obtained an increase of 25% from cycle I, namely with an average percentage of 89%. percentage of 89% Thus, the research conducted shows that the application of interactive learning based on articulate storyline 3 can increase student motivation to learn Indonesian narrative story material from pre-cycle to cycle II with an increase of 10% increase.